PENGARUH PEMBERIAN PUPUK UREA TERHADAP PERTUMBUHAN DAN HASIL KEDELAI HITAM PADA TANAH ALUVIAL - ALIAMIN, ALIAMIN; SULISTYOWATI, HENNY; GUSMAYANTI, EVI (Jurnal Sains Mahasiswa Pertanian, 2019)
PENGARUH PEMBERIAN PUPUK UREA TERHADAP PERTUMBUHAN DAN HASIL KEDELAI HITAM PADA TANAH ALUVIAL THE EFFECT OF GIVING UREA FERTILIZER ON GROWTH AND YIELD OF BLACK SOYBEAN ON ALUVIAL SOIL Aliamin(1), Henny Sulistyowati (2), Evi Gusmayanti(2) (1) Faculty of Agriculture and(2) Lecturer in the Faculty of Agriculture, Tanjungpura University Pontianak ABSTRACT This study aimed to obtain the best dossage of urea fertilizer on the growth and yield of black soybean cultivated on alluvial soil. This research was conducted at experimental farm in Faculty of Agriculture. Tanjungpura University Pontianak from May 2018 to August 2018. There were five levels of treastment, i.e. u0 = 0 kg urea/ha, u1 = 25 kg / ha or equivalent to 0.2 g / polybag, u2 = 50 kg / ha or equivalent to 0.4 g / polybag, u3 = 75 kg / ha or equivalent to 0.6 g / polybag and u4 = 100 kg / ha or equivalent to 0.8 g / polybag. Each treatment consistedof five replicates and four samples, hence there were 100 polybags in total. The polybags were arangged according completely randomized design (CRD). The study showed that dosage variation of urea fertilizer results the similar value of observed variables, i.e. roots volume, dry biomass, plant height and weight dry seeds of plant. However, the dosage variation of urea fertilizer has an impact to the weight of a 100 dry seeds. It seemed that the dosage of 50 kg urea/ha or equivalent to 0.4 g / polybag is the best dosage for planting black soybean in alluvial soil.Keywords: Alluvial soil, black soybean, urea fertilizer.